Pengukuran Kualitas Hidup Penderita Hipertensi Menggunakan Instrumen EQ-5D-5L - Abang Raffli; Muhammad Akib Yuswar; Shoma Rizkifani (Journal Syifa Sciences and Clinical Research, 2023)
Hypertension can affect the quality of life. Poor quality of life is caused by complications with comorbid conditions such as heart disease, kidney disease, and diabetes mellitus. Hypertension occurs when a person's blood pressure is above the normal or optimal limit, namely 120 mmHg for systolic and 80 mmHg for diastolic. This study aims to determine the quality of life of patients with hypertension. This research is an observational study with a prospective cross sectional study design. Data were collected by purposive sampling at the x Health Center that met the inclusion criteria using the European Quality of Life 5 Dimensions 5 level (EQ5D5L) Questionnaire instrument. The data is then converted into a single summary index using the index calculator EQ 5D. From the results of the study, there were 68 cases of hypertension that matched the inclusion criteria, based on gender, it was dominated by 70.5% women with ages 55 to 65 years by 82% with the highest index score percentage 1 (29.41%) and the lowest 0.592. (8.82%) Measuring the quality of life of hypertensive patients at the x Health Center using the EQ5D5L instrument is categorized as good if the EQ5D5L index obtained is 0.5.